Implementasi Program KKN dalam Perancangan dan Pemasangan Plang Jalan Guna Meningkatkan Identifikasi Wilayah di Desa Tambun, Kecamatan Tambun Selatan - Amanda Azizah; Selina Permata; Elysza Azzahra; Agnesya Delvia; Rifaldi Adhitama; Arsahlan Nasrullah; Muhammad Zanuar (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
The Community Service Program (KKN) is a form of community engagement aimed at addressing real-world problems in society through collaborative and sustainable solutions. One of the issues identified in Tambun Village, South Tambun District, is the lack of directional signage, which affects regional identification, accessibility, and community mobility efficiency. This activity aims to design and install road signs as a visual information medium to improve navigation systems, facilitate public access, and strengthen regional identity. The implementation method uses a participatory approach involving several stages, including field observation, problem identification, design planning, production, and installation of road signs in strategic locations. The results indicate that the installation of signage at Gang H. Saman, Pekopen Bulak Street, and Kebon Banteng Street has improved location accessibility, facilitated address identification for residents and visitors, and increased community awareness regarding environmental identity. Furthermore, this program demonstrates the importance of community participation in developing basic infrastructure that supports daily activities. Therefore, this initiative contributes significantly to community-based infrastructure development and provides practical benefits for improving local information systems and public services.